Hard-Bottom Megabenthic Communities of a Chilean Fjord System: Sentinels for Climate Change? - Betti, Federico; Enrichetti, Francesco; Bavestrello, Giorgio; Costa, Andrea; Moreni, Alessandra; Bo, Marzia; Ortiz Saini, Paula; Daneri, Giovanni (Frontiers in Marine Science, 2021)
Chilean Patagonia hosts one of the extensive fjord systems in the world, spanning more than 1600 km between 41–55°S, and with a complex geomorphology and hydrography that supports rich and unique assemblages of marine fauna. The biodiversity of benthic organisms is possibly further enhanced by the geographic position of the region that extends far south into subantarctic waters. However, we currently lack an exhaustive picture of the zonation and ecological functioning of the benthic communities within Chilean fjords. The present study provides a detailed examination of the hard substrata megabenthic communities inhabiting the Puyuhuapi and Jacaf fjord system, in the Aysén Region of Chile. Fifty-nine stations scattered along these fjords were explored through SCUBA diving surveys, at depths between 5 and 30 m, and 16 stations were characterized in terms of benthic cover and diversity using replicated underwater photography. Ten hard bottom megabenthic communities were identified within the fjords, with some communities newly described for this region. Community composition varied both along-fjord, and with depth, and was apparently driven by variation in environmental properties. Our characterization of these fjord communities improves overall knowledge of the functioning of the fjords, and provides a useful baseline against which future anthropogenic pressures can be assessed. Future shifts in bathymetric and geographical distributions might indicate detrimental effects of climate changes, and we therefore propose that characteristic communities could be adopted as “sentinels” for overall environmental status of these unique fjord ecosystems. In this regard, detailed mapping of the distribution of megabenthic communities can provide a fundamental tool that assists in best management practices for these ecosystems.